Investigation of artisanal tanning in Lesotho communities using a Setlokoa cowhide dress as a case study - McGinn, Isabelle (University of Pretoria, 2022)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2021.